Crossed-Brain Representation of Verbal and Nonverbal Functions - Esmeralda Matute; Alfredo Ardila; Monica Rosselli; Jahaziel Molina Del Rio; Ramiro López Elizalde; Manuel López; Angel Ontiveros (Case Reports in Neurological Medicine)
A 74-year-old, left-handed man presented with a rapidly evolving loss of strength in his right leg associated with difficulty in walking. MR images disclosed an extensive left hemisphere tumor. A neuropsychological examination revealed that language was broadly normal but that the patient presented with severe nonlinguistic abnormalities, including hemineglect (both somatic and spatial), constructional defects, and general spatial disturbances; symptoms were usually associated with right hemisphere pathologies. No ideomotor apraxia was found. The implications of crossed-brain representations of verbal and nonverbal functions are analyzed.